What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques